PERAN BPRS DALAM PERKEMBANGAN DAN PERTUMBUHAN UMKN DI INDONESIA - M. Danial Farkhani; Muhammad Za'im Ulhaq; Ibrahim Abdusalam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Because Micro, Small, and Medium Enterprises (MSMEs) are an important part of the Indonesian economy, the role of Sharia People Credit Bank (BPRS) is crucial in supporting the growth and advancement of MSMEs. As a sharia financial institution, BPRS has a strategic goal to enhance financing inclusion while adhering to sharia principles that align with the needs of the community. Due to the lack of collateral and high business risks, MSMEs often struggle to obtain financing from conventional banks. On the other hand, BPRS provides more flexible financing products based on profit-sharing, murabahah, or ijarah, which enable SMEs to grow. BPRS not only provides capital in this situation but also acts as a strategic partner for SMEs to manage their businesses, increase production capacity, and expand market networks. BPRS can gain greater trust among MSME actors, most of whom are Muslim, by using an approach based on Sharia values. BPRS also helps with economic stability and local welfare. This article discusses how BPRS can accelerate the growth of small and medium enterprises (SMEs) in Indonesia by providing easier and more sustainable access to financing. It also discusses the challenges and opportunities faced while fulfilling that role.